Frecuencia de aplicación de fertilizante foliar orgánico en sandia (Citrullus lanatus Th) var. Charleston Gray en Zungarococha - Iquitos - Rios Lopez, Franklin (2012)
The study has been carried out to determine the effect of the application frequency of an organic foliar fertilizer (Biol) and its influence on the production of the watermelon crop (Citrillus lanatus Th). A Complete Random Block Design was used, with 5 treatments and 4 repetitions. The evaluation was made 90 days after sowing, evaluating 8 plants per treatment. The evaluation of the results shows us that the higher the frequency of application of organic foliar fertilizer (Biol) in the "Watermelon (Citrullus lanatus Th) crop, Charleston Gray variety", the yield increases. The yield per hectare of the T1 treatment (Every 3 days of application) and the T2 treatment (Every 6 days of application), occupied the first places with 36,596.34 kilograms per hectare, and 29,497.05 kilograms per hectare, respectively, with the treatment occupying the last place. T0 with 5,110.60 kilograms per hectare.